Application of Good Corporate Governance Principles Based on Catur Purusa Artha in Village Credit Institutions - Pramuki, Ni Made Wisni Arie; Andayani W, Rai Dwi; Yuliantari, Ni Putu Yeni (INTERNATIONAL JOURNAL OF TRENDS IN ACCOUNTING RESEARCH, 2025)
This study aims to comprehensively describe the application of the principles of Good Corporate Governance (GCG) based on the local cultural values of Catur Purusa Artha in the management of Village Credit Institutions (VCI) in Kerobokan Traditional Village, Bali. This study uses a qualitative descriptive approach with a single case study, involving the main informants such as the Customary Village, the Head of VCI, and the Internal Supervisory Agency as primary data sources. Data was collected through structured in-depth interviews based on indicators of transparency, accountability, responsibility, independence, and fairness according to GCG standards, contextualized with Balinese Hindu teachings through the concept of Catur Purusa Artha (dharma, artha, kama and moksa). The data analysis follows the Miles & Huberman interactive model with the stages of data reduction, data presentation, and conclusion verification. The results of the study revealed that most of the GCG principles have been effectively implemented in VCI Kerobokan with the integration of local cultural values as the foundation of operational ethics. Transparency is realized through information disclosure in customary village meetings; accountability is carried out by internal supervisory bodies; Independence is enforced through a collective consensus mechanism; fairness is reflected in the credit policy of small business priorities; and social responsibility based on dharma and moksa as moral guidelines for institutional managers. However, there are significant obstacles in the remuneration system that are not fully fair and transparent according to individual contributions and limitations in the socialization of work plans to all indigenous capital owners due to limited human resources and communication media.